Government budgeting - Kumar, Anil
A government budget is a document prepared by the government and/or other political entity presenting its anticipated tax revenues (inheritance tx, income tax, corporation tax, import taxes) and proposed spending/expenditure (Healthcare, Education, Defence, Roads, State Benefit) for the coming financial year. In most parliamentary systems, the budget is presented to the legislature and often requires approval of the legislature. Govenrment budget, forecast by a government of its expenditures and revenues for a specific period of time. In national finance, the period covered by a budgetis usually a year, known as a fianncial or fiscal year, which may or may not correspond with the calendar year. The word budget is derived from the old French bouget ("little bag"). When the British Chancellor of the Exchequer makes his annual finacial statement, he said to "open" his budget, or receptacle of documents and accounts. Government budget have economic, political and technical basis. Unlike a pure economic budget, they are not entirely designed to allocate scarce resources for the best economic use. Government budgets also have a political basis wherein different interests push and pull in an attempt to obtain benefits and avoid burdens. The technical element is the forecast of the likely levels of revenues and expenses. A military budget (or military expenditure), also known as a defense budget, is the amount of financial resources dedicated by an entity (most often a nation or a state), to raising and maintaining an armed forces. This book makes an interesting reading for historians, defence and policy analysts, researchers and general readers alike.